Evaluation of economic feasibility studies for tourism hotel projects in Sulaymaniyah Governorate: Ramada Hotel as a case study - Ali Jalal Hussein; Mohammed Aras Ali (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
The main objective of this study is to showing the importance of Feasibility studies for Tourism Hotels projects, highlighting the weakness point and neglected aspects of Feasibility studies carried out for the Hotels in the province of Sulaimani. Through using of several approaches to reporting assumptions including the descriptive and analytical and the study found a number of conclusions, including the lack of benefit the tourism and the hospitality authority of the economic feasibility to achieve economic development. This is due to a number of factors, and the obstacles that have combined to marginalize the role of economic feasibility as a method to ensure the success of investments Hotel, and the lack of awareness among investors and businessmen of the importance of economic feasibility studies before starting the construction of the project. Moreover, the study proposed, activating the role of feasibility studies to achieving economic development, through the establishment of consulting firms under the supervision of specialists and experts in this field, and the increasing awareness among investors and businessmen through courses and seminars to show the importance of preparing feasibility studies as a means for the success of their projects.